Relationship of Knowledge on Respiratory Disorders with Lung Function in Masons in East Surabaya - Amelia Lorensia; Rivan Virlando Suryadinata; Wilma Adib Gardiawan (Journal of Tropical Pharmacy and Chemistry, 2021)
Masons are regularly exposed to air pollution in the workplace The pollution exposure received by them is a risk factor for respiratory problems. Most of the masons had insufficient knowledge that is very important for the management of a person's illness. The purpose of this study was to determine relationship of knowledge on respiratory disorders with lung function in masons in east surabaya. This research was an observational study with a cross-sectional design with a purposive method.The research was conducted from April to July 2019 in the East Surabaya area. The variables that will be observed in this study are the level of knowledge of risk factors, symptoms, and treatment and therapy regarding respiratory disorders. In this study, there were 158 respondents consisting of 79 groups with impaired lung function and 79 groups without lung function disorders. Most of the level of knowledge of both groups was good in risk factors and treatment of respiratory disease, but instead on the symptoms regarding respiratory disease. The research showed that there was a relationship between the level of knowledge about risk factors for respiratory disease (p(0.223)<0.05) and lung function, but there was no difference in knowledge about symptoms (p(0.745)<0.05) and treatment (p(0.741)<0.05) respiratory disease with pulmonary function. Therefore, it was necessary to plan further educational programs in increasing masons' knowledge of respiratory symptoms so that they could catch respiratory diseases earlier.